2008
DOI: 10.1063/1.2913764
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling study of cavity grade Nb: Possible magnetic scattering at the surface

Abstract: Tunneling spectroscopy was performed on Nb pieces prepared by the same processes used to etch and clean superconducting radio frequency (SRF) cavities. Air exposed, electropolished Nb exhibited a surface superconducting gap Δ=1.55 meV, characteristic of clean, bulk Nb. However the tunneling density of states (DOS) was broadened significantly. The Nb pieces treated with the same mild baking used to improve the Q-slope in SRF cavities, reveal a sharper DOS. Good fits to the DOS were obtained using Shiba theory, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 21 publications
6
45
0
Order By: Relevance
“…This can be significant as it has been shown that <3% oxygen vacancies in Nb 2 O 5 change this compound from a nonmagnetic insulator to a conductor with localized magnetic moments [15]. The superconducting gap region probed by tunneling sometimes exhibits a smeared density of states consistent with pair breaking due to magnetic scattering [16]. There is thus a good chance that the source of rf dissipation in a pit is tied to the local chemistry (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This can be significant as it has been shown that <3% oxygen vacancies in Nb 2 O 5 change this compound from a nonmagnetic insulator to a conductor with localized magnetic moments [15]. The superconducting gap region probed by tunneling sometimes exhibits a smeared density of states consistent with pair breaking due to magnetic scattering [16]. There is thus a good chance that the source of rf dissipation in a pit is tied to the local chemistry (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2b Si-interface thickness), which could create a metallic silicide at the Nb/Si interface. Oxygen traces migrating through the silicon capping layer could also further contribute to the inverse proximity effect since niobium oxides with low stoichiometry are known to be metallic and even suspected to be a potential source of destruction of superconductivity by magnetic effects 29 .…”
Section: Inverse Proximity Effect Induced By the Capping Layermentioning
confidence: 99%
“…Given the above properties, it was recently argued in Ref. 16 that they could indeed be attributed to the presence of magnetic impurities in the system. Although the bulk of Nb samples used for SRF cavities is typically very clean, a disordered oxide surface layer forms due to exposure to atmosphere 14 , Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning tunneling spectroscopy measurements of the SRF cavity samples performed in Ref. 16 revealed the surface tunneling DOS with appreciable "subgap" contribution, consider- , and (4.17) of the paper by numerically calculating the integrals over and k. In the gapped regime (e), R(ω) ∝ exp(−∆ * /T ) is exponential at lower temperatures and vanishes at T = 0. In the gapless regime (f), for moderate "subgap" DOS, the surface resistance R(ω) is exponential at lower but finite temperatures and saturates to a nonzero value at T = 0.…”
Section: Introductionmentioning
confidence: 99%